2021
DOI: 10.1007/s10488-021-01163-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Racial/Ethnic Equity in College Student Mental Health Through Innovative Screening and Treatment

Abstract: Although college campuses are diversifying rapidly, students of color remain an underserved and understudied group. Online screening and subsequent allocation to treatment represents a pathway to enhancing equity in college student mental health. The purpose of the current study was to evaluate racial/ethnic differences in mental health problems and treatment enrollment within the context of a largescale screening and treatment research initiative on a diverse college campus. The sample was comprised of n = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The academic year of study of the college students has also been shown to impact academic stress levels (Misra and McKean, 2000 ; Elias et al, 2011 ; Wyatt et al, 2017 ; Liu, C. H., et al, 2019 ; Defeyter et al, 2021 ). While several studies indicate that racial/ethnic minority groups of students, including Black/African American, Hispanic/Latino, and Asian American students, are more likely to experience anxiety, depression, and suicidality than their white peers (Lesure-Lester and King, 2004 ; Lipson et al, 2018 ; Liu, C. H., et al, 2019 ; Kodish et al, 2022 ), these studies are limited and often report mixed or inconclusive findings (Liu, C. H., et al, 2019 ; Kodish et al, 2022 ). Therefore, more studies should be conducted to address this gap in research to help identify subgroups that may be disproportionately impacted by academic stress and lower well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The academic year of study of the college students has also been shown to impact academic stress levels (Misra and McKean, 2000 ; Elias et al, 2011 ; Wyatt et al, 2017 ; Liu, C. H., et al, 2019 ; Defeyter et al, 2021 ). While several studies indicate that racial/ethnic minority groups of students, including Black/African American, Hispanic/Latino, and Asian American students, are more likely to experience anxiety, depression, and suicidality than their white peers (Lesure-Lester and King, 2004 ; Lipson et al, 2018 ; Liu, C. H., et al, 2019 ; Kodish et al, 2022 ), these studies are limited and often report mixed or inconclusive findings (Liu, C. H., et al, 2019 ; Kodish et al, 2022 ). Therefore, more studies should be conducted to address this gap in research to help identify subgroups that may be disproportionately impacted by academic stress and lower well-being.…”
Section: Introductionmentioning
confidence: 99%
“…For college students, the COVID-19 pandemic has resulted in significant changes and disruptions to daily life, elevated stress levels, and mental and physical health deterioration (American Psychological Association, 2020 ; Husky et al, 2020 ; Patsali et al, 2020 ; Son et al, 2020 ; Clabaugh et al, 2021 ; Lee et al, 2021 ; Lopes and Nihei, 2021 ; Yang et al, 2021 ). While any college student is vulnerable to these stressors, these concerns are amplified for members of minority groups (Salerno et al, 2020 ; Clabaugh et al, 2021 ; McQuaid et al, 2021 ; Prowse et al, 2021 ; Kodish et al, 2022 ). Identifying students at greatest risk provides opportunities to offer support, resources, and mental health services to specific subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, populations with a migration background are at greater risk of mental health problems than native populations, especially depression, post-traumatic stress disorder (PTSD), and anxiety (Ekeberg & Abebe, 2021 ; Mindlis & Boffetta, 2017 ; Missinne & Bracke, 2012 ). Access to appropriate treatment and referral to relevant mental health services have been shown to be limited for migrants (Bhui et al, 2018 ; Giacco et al, 2014 ; Kodish et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important given the fact that low perceived need is a common help-seeking barrier [ 5 ]. In addition, universal screening is an approach by which all students may have an equal opportunity for early identification and service acquisition [ 15 ] and may offer an effective strategy for reaching equity-seeking groups (eg, racialized, disabled, gender, and sexual minority groups) [ 8 , 16 - 18 ]. In a campus-wide universal screening campaign open to all students, Kodish et al [ 16 ] observed substantial participation of a racially diverse student population (73.3%).…”
Section: Introductionmentioning
confidence: 99%